Reconciling contradictions: Buddhist-Muslim violence, narrative making and memory in Myanmar - Schissler, M; Walton, M; Thi, P (Routledge, 2017)
Myanmar has been the site of serious violence between Buddhist and Muslim communities. This article presents findings from a research project convened to better understand the production of this violence. Based on interviews with 78 residents of six cities, we find a narrative that presents Islam in general and Muslims in Myanmar as an existential threat to “race and religion” and a personal threat to individuals and communities. This narrative is reinforced by three inter-related sets of arguments that refer to international events, events within Myanmar, and personal experiences. Drawing on these findings, we explore the ways in which Muslims in Myanmar are constructed as a “fearsome Other,” thus justifying discrimination and violence. However, we also identify alternative narratives that contest the production of violence. These narratives are generated through articulated senses of contradiction between contemporary antagonisms and memories of inter-religious co-existence. We argue that understanding these narratives is one necessary part of much larger efforts to promote peace and reconciliation.